Hatred and violence in light of Emmanuel Levinas' disinterested responsibility - Santiago-Espartinez, Alma (2013)
This article is a rethinking of the status of the subject in relation to one's responsibility to the Other and on how the latter affects the former with an overarching objective of acquiring the complete reality of the person. It initially examines Emmanuel Levinas' disinterested responsibility which describes the ethical relation between the I and the Other, giving primacy to the other. Secondly,it outlines carefully Levinas' concept of justice which announces the entrance of the Third. Thirdly, it presents the conditions under which violence is justified and the constraints within which such measures can be introduced. Finally, it attempts to establish the connection between Levinasian concept of justice and the wisdom of forgiveness - an idea Levinas did not address directly in his philosophical works but which can be perceived as a valid response to honoring, rather than canceling out, justice.
Keywords: Violence